JAVANESE MEDICINAL MEASURE LEXICONS (NUMERAL CLASSIFIERS) IN SERAT PRIMBON RERACIKAN JAMPI JAWI - Sinungharjo, F.X.; Adji, S.E. Peni; Adji, F. Tjandrasih (International Journal of Humanity Studies (IJHS), 2023)
Traditional medicine in a global context has been observed widely in several countries. Research on traditional medicine has not been massively conducted in Indonesia, especially in Java. The present research, in response to the area of this subject, is an initial study to observe and examine the traditional medicine in Java, especially the medicine measurement system recorded in Serat Primbon Racikan Jampi Jawi. The measure system in traditional medicine has various lexicons as has been revealed in the lexicalization of numeral classifiers and the cultural context of the measurement system in traditional medicine recorded in Serat Primbon Racikan Jampi Jawi. The theoretical perspectives are composed of culture, semantics, and lexicography; using note-taking techniques as the data collection, dictionary method as the data analysis, definition and meaning description as the data presentation as well as its meaning relations. Based on the observation, there were 77 (seventy-seven) Javanese measure lexicons consisting of 60 (sixty) base words, 5 (five) affixed words, and 13 (thirteen) word combinations in Serat Primbon Racikan Jampi Jawi. Meaning relations found from the lexicons were abstract meaning relations by using 7 (seven) concepts of retrieval and concrete features with 6 (six) compositional constructions. The measure was obtained from 9 (nine) other fields of lexicon and was used to measure 25 (twenty-five) types of ingredients with one-to-one relations, one-to-two or more relations, and two or more-to-one relations. This research indicated that (1) The form of language adapts to the creativity and references in the measure; (2) The meaning of the measure characterizes the experience and knowledge of the Javanese people on the traditional medicine system in their everyday life; and (3) The measure system is the answer to the needs, specifications, and inheritance of the local wisdom of the Javanese people, particularly in the field of traditional medicine.